The Christ of the prophets - Robertson, O. Palmer (Phillipsburg, NJ Presbyterian and Reformed, 2004)
Includes bibliograqhical references and indexes.
Sequel to : The Christ of the covenants, which see also.
Keywords: Bible O.T. Prophets -- criticism, interpretation, etc; Bible O.T. Prophets -- biblical teaching